2013
DOI: 10.1186/1471-2334-13-222
|View full text |Cite
|
Sign up to set email alerts
|

“Induced sputum versus gastric lavage for the diagnosis of pulmonary tuberculosis in children”

Abstract: BackgroundDiagnosis of pulmonary tuberculosis (PTB) is difficult in infants and young children. For microbiological confirmation of PTB children, sequential gastric lavage (GL) is recommended. Induced sputum (IS) may be an alternative or complementary tool, but the information is limited in children in developed countries. The aim of this study is to assess the safety and diagnostic yield from IS combined with GL for PTB diagnosis in non-HIV infected children.MethodsThe study involved 22 children with suspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
7
16
0
3
Order By: Relevance
“…Previous studies have shown high sensitivity of Xpert when sputum,6–8 gastric lavage,9,10 bronchoalveolar lavage11 and nasopharyngeal aspirates12 were used. Xpert was therefore endorsed by the World Health Organization as an initial test for diagnosing TB in children.…”
mentioning
confidence: 99%
“…Previous studies have shown high sensitivity of Xpert when sputum,6–8 gastric lavage,9,10 bronchoalveolar lavage11 and nasopharyngeal aspirates12 were used. Xpert was therefore endorsed by the World Health Organization as an initial test for diagnosing TB in children.…”
mentioning
confidence: 99%
“…[5][6][7][8] The availability of isolation rooms with negative pressure required for SI, and the presence of bronchoscopy facilities only in specialised hospital settings, however, hinders the wider use of these procedures in resource-limited settings. GA is commonly used in children to obtain sputum specimens, 6,[8][9][10][11][12][13] but is less common in adults with difficulties in expectoration.…”
mentioning
confidence: 99%
“…5 The diagnosis of PTB in children remains challenging, partly due to the inability of children <8 years to generate a productive sputum specimen 17 and because of their paucibacillary nature. 18 The majority (70%) of our study subjects were children <5 years of age. Thus, in typical HIV care and treatment settings in Africa, our methods of PTB diagnosis would be considered more representative since routine sputum or gastric aspirate smear microscopy is uncommon.…”
Section: Discussionmentioning
confidence: 99%